Evaluation of preoperative visual pathway impairment in patients with non-functioning pituitary adenoma using diffusion tensor imaging coupled with optical coherence tomography - Pang, Yanhua; Tan, Zhi; Chen, Xinxin; Liao, Zhihui; Yang, Xin; Zhong, Qin; Huang, Baqi; Zhong, Qianshuo; Zhong, Jingxiang; Mo, Wei (Frontiers in Neuroscience, 2023)
Objective Optic chiasma compression and associated visual impairment induced by a non-functioning pituitary adenoma (NFPA) is commonly assessed by the optic disk and retina but is inadequate to understand the entire visual pathway impairment. We aim to evaluate the use of optical coherence tomography (OCT) coupled with diffusion tensor imaging (DTI) for the preoperative evaluation of visual pathway impairment. Methods Fifty-three patients with NFPA (categorized into mild and heavy compression subgroups) were subjected to OCT to calculate the thickness of the circumpapillary retinal nerve fiber layer (CP-RNFL), macular ganglion cell complex (GCC), macular ganglion cell layer (GCL), and macular inner plexus layer (IPL), as well as to DTI to calculate the fractional anisotropy (FA) and apparent diffusion coefficient (ADC) values. Results Compared to mild compression, heavy compression caused decreased FA value, increased ADC value of several segments of the visual pathway, thin temporal CP-RNFL, and quadrant macular GCC, IPL, and GCL. Average CP-RNFL thickness, inferior-macular inner-ring IPL and GCC thicknesses, inferior CP-RNFL thickness, and superior CP-RNFL thickness were the best indicators of the impairment of the optic nerve, optic chiasma, optic tract, and optic radiation, respectively. Conclusion DTI and OCT parameters can effectively evaluate visual pathway impairment and are beneficial for the objective preoperative evaluation of visual pathway impairment in patients with NFPA.